Taxifolin increased semen quality of Duroc boars by improving gut microbes and blood metabolites - Zhou, Yexun; Chen, Liang; Han, Hui; Xiong, Bohui; Zhong, Ruqing; Jiang, Yue; Liu, Lei; Sun, Haiqing; Tan, Jiajian; Cheng, Xiaowei; Schroyen, Martine; Gao, Yang; et al. (Frontiers in Microbiology, 2022)
Taxifolin (TAX), as a natural flavonoid, has been widely focused on due to its strong anti-oxidation, anti-inflammation, anti-virus, and even anti-tumor activity. However, the effect of TAX on semen quality was unknown. The purpose of this study was to analyze the beneficial influences of adding feed additive TAX to boar semen in terms of its quality and potential mechanisms. We discovered that TAX increased sperm motility significantly in Duroc boars by the elevation of the protein levels such as ZAG, PKA, CatSper, and p-ERK for sperm quality. TAX increased the blood concentration of testosterone derivatives, antioxidants such as melatonin and betaine, unsaturated fatty acids such as DHA, and beneficial amino acids such as proline. Conversely, TAX decreased 10 different kinds of bile acids in the plasma. Moreover, TAX increased “beneficial” microbes such as Intestinimonas, Coprococcus, Butyrivibrio, and Clostridium_XlVa at the Genus level. However, TAX reduced the “harmful” intestinal bacteria such as Prevotella, Howardella, Mogibacterium, and Enterococcus. There was a very close correlation between fecal microbes, plasma metabolites, and semen parameters by the spearman correlation analysis. Therefore, the data suggest that TAX increases the semen quality of Duroc boars by benefiting the gut microbes and blood metabolites. It is supposed that TAX could be used as a kind of feed additive to increase the semen quality of boars to enhance production performance.